A STUDY ON FACTORS INFLUENCING THE DECISION MAKING BEHAVIOR IN PURCHASING VEHICLE INSURANCE SERVICES - Batsaikhan, Sugarjav; Gantulga, Urandelger (Journal of Business and Innovation (Бизнес & Инноваци), 2026)
Despite the experienced significant growth of the insurance sector in Mongolia, particularly in motor vehicle insurance, there remains a paucity of comprehensive research examining the key factors influencing consumers’ (drivers and vehicle owners) purchase intentions in selecting and purchasing insurance services, as well as the interrelationships among these factors. This study aims to identify the determinants affecting consumers’ decision-making regarding motor vehicle insurance purchases. A total of 340 respondents participated in the study, and six hypotheses were tested using SPSS 27.0. The results indicate that an insurance company’s reputation, consumer trust, and advertising exert a positive influence on consumers’ purchase intentions. Conversely, the hypothesized positive effects of compensation processing time, ease of obtaining insurance, and perceived insurance benefits on purchase intention were not supported. These findings provide valuable insights for insurers seeking to enhance consumer engagement and inform strategic marketing decisions in the Mongolian insurance market.